Parental socioeconomic and psychological determinants of the 2009 pandemic influenza A(H1N1) vaccine uptake in children - Salo-Tuominen Krista; Teros-Jaakkola Tamara; Toivonen Laura; Ollila Helena; Rautava Päivi; Aromaa Minna; Lahti Elina; Junttila Niina; Peltola Ville (ELSEVIER SCI LTD, 2022)
Background: Before COVID-19, the previous pandemic was caused by influenza A(H1N1)pdm09 virus in 2009. Identification of factors behind parental decisions to have their child vaccinated against pandemic influenza could be helpful in planning of other pandemic vaccination programmes. We investigated the association of parental socioeconomic and psychosocial factors with uptake of the pandemic influenza vaccine in children in 2009–2010.
Methods: This study was conducted within a prospective birth-cohort study (STEPS Study), where children born in 2008–2010 are followed from pregnancy to adulthood. Demographic and socioeconomic factors of parents were collected through questionnaires and vaccination data from electronic registers. Before and after the birth of the child, the mother’s and father’s individual and relational psychosocial well-being, i.e. depressive symptoms, dissatisfaction with the relationship, experienced social and emotional loneliness, and maternal anxiety during pregnancy, were measured by validated questionnaires (BDI-II, RDAS, PRAQ, and UCLA).
Results: Of 1020 children aged 6–20 months at the beginning of pandemic influenza vaccinations, 820 (80%) received and 200 (20%) did not receive the vaccine against influenza A(H1N1)pdm09. All measures of parents’ psychosocial well-being were similar between vaccinated and non-vaccinated children. Children of younger mothers had a higher risk of not receiving the influenza A(H1N1)pdm09 vaccine than children of older mothers (OR 2.59, 95% CI 1.52–4.43, for mothers < 27.7 years compared to ≥ 33.6 years of age). Children of mothers with lower educational level had an increased risk of not receiving the vaccine (OR 1.46, 95% CI 1.00–2.14).
Conclusions: Mother’s younger age and lower education level were associated with an increased risk for the child not to receive the 2009 pandemic influenza vaccine, but individual or relational psychosocial well-being of parents was not associated with children’s vaccination. Our findings suggest that young and poorly educated mothers should receive targeted support in order to promote children’s vaccinations during a pandemic.